Four new species of Noeetomima Enderlein (Diptera: Lauxaniidae), with a key to world species - Shi, Li; Gaimari, Stephen; Yang, Ding (Zootaxa, 2013)
The following four species are described as new to science: Noeetomima chinensis sp. nov. (China), N. jinpingensis sp. nov. (China, Nepal), N. tengchongica sp. nov. (China) and N. yunnanica sp. nov. (China). The species Noeetomima aberrans Shatalkin and N. nepalensis Stuckenberg are newly recorded for Japan and India, respectively, and the male genitalia for N. thaiensis Sasakawa are described and illustrated for the first time. A key to separate world species is presented, as is a detailed checklist of all species.